Editorial Paper: Integrated Simulation and Virtual Space in Digital Architecture: Bridging Innovation, Aesthetics, and Sustainability in The Metaverse Era - Purwanto, L.M.F (JoDA Journal of Digital Architecture, 2025)
INTEGRATED SIMULATION AND VIRTUAL SPACE IN DIGITAL ARCHITECTURE: BRIDGING INNOVATION, AESTHETICS, AND SUSTAINABILITY IN THE METAVERSE ERA